Medical Imaging 2017: Imaging Informatics for Healthcare, Research, and Applications 2017
DOI: 10.1117/12.2253889
|View full text |Cite
|
Sign up to set email alerts
|

Initial simulated FFR investigation using flow measurements in patient-specific 3D printed coronary phantoms

Abstract: Purpose Accurate patient-specific phantoms for device testing or endovascular treatment planning can be 3D printed. We expand the applicability of this approach for cardiovascular disease, in particular, for CT-geometry derived benchtop measurements of Fractional Flow Reserve, the reference standard for determination of significant individual coronary artery atherosclerotic lesions. Materials and Methods Coronary CT Angiography (CTA) images during a single heartbeat were acquired with a 320×0.5mm detector ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Previous conference proceedings from this study have shown the significant impact of distal resistance on the measured FFR values. 25 Simulation of the capillary bed effect on flow is not possible with the current 3D printing technologies; while 3D printing resolution would allow creation of very fine structures, removal of support material would be very challenging. Hence, distal resistance can be simulated within reasonable ranges by controlling the diameter of the outflow tubes with mechanical clamps for each coronary artery.…”
Section: Flow Experimentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous conference proceedings from this study have shown the significant impact of distal resistance on the measured FFR values. 25 Simulation of the capillary bed effect on flow is not possible with the current 3D printing technologies; while 3D printing resolution would allow creation of very fine structures, removal of support material would be very challenging. Hence, distal resistance can be simulated within reasonable ranges by controlling the diameter of the outflow tubes with mechanical clamps for each coronary artery.…”
Section: Flow Experimentationmentioning
confidence: 99%
“…25 These two flow controls were adjusted in conjunction until pressure within the aorta reached a minimum of 80 mmHg to ensure physiological accuracy. 22,25,26 Previous in vitro studies using idealized 3D printed coronary phantoms have indicated a dependence on FFR with increasing aortic pressure, making this adjustment in the 3D printed phantoms a necessary step toward replicating physiological conditions. 16 Figure 4(a) shows the setup of the phantoms within the flow loop and Fig.…”
Section: Flow Experimentationmentioning
confidence: 99%
“…FFR measures blood flow conditions by invasively navigating a pressure wire through the artery and reading out a ratio of the pressure both proximal and distal to the stenosis. 3,4 This method allows for lesions of intermediate stenosis to be better analyzed with regards to hemodynamics. Typically, a threshold FFR ratio of 0.8 determines whether or not a stent will be used to treat the stenosis.…”
Section: Description Of Purposementioning
confidence: 99%
“…Geometry extension and inclusion of pathologies such as atherosclerotic plaques or surrounding anatomical structures gives rise to 3D printed models in which flow measurements can be accurately tested 4 . This study leverages 3D printing to build patient specific phantoms that closely mimic the arterial wall mechanics as a validation tool for a diagnostic software.…”
Section: Description Of Purposementioning
confidence: 99%
See 1 more Smart Citation